Dielectric Properties of SnO2 Thin Film Using SPR Technique for Gas Sensing Applications. (6th May 2014) - Paliwal, Ayushi; Sharma, Anjali; Tomar, Monika; Gupta, Vinay
Abstract : Focus has been made on the determination of dielectric constant of thin dielectric layer (SnO2 thin film) using surface plasmon resonance (SPR) technique and exploiting it for the detection of NH3 gas. SnO2 thin film has been deposited by rf-sputtering technique on gold coated glass prism (BK-7) and its SPR response was measured in the Kretschmann configuration of attenuated total reflection using a p-polarised light beam at 633 nm wavelength. The SPR response of bilayer film was fitted with Fresnel's equations in order to calculate the dielectric constant of SnO2 thin film. The air/SnO2 /Au/prim system has been utilized for detecting varying concentration (500 ppm to 2000 ppm) of NH3 gas at room temperature using SPR technique. SPR curve shows significant shift in resonance angle from 44.8° to 56.7° on exposure of fixed concentration of NH3 gas (500 ppm to 2000 ppm) with very fast response and recovery speeds.